Efektifitas Sistem Absensi Fingerprint dan Manual dalam Menerapkan Kedisiplinan : (Studi Komparatif pada Karyawan Tetap dan Magang) - Baitulloh, Sabit; Andriani; Ghofur, Muh. Abdul (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study is intended to analyze the difference in the effectiveness of fingerprint and manual attendance systems in implementing discipline, a comparative study on permanent employees and interns at Pusat Oleh-Oleh Gudange Tahu Takwa / CV. GTT Kediri. The research method used is qualitative with a case study approach and a comparative study on permanent employees and interns. Data collection instruments used observation, interviews, and documentation. The application of fingerprint attendance for permanent employees and manuals for interns has differences. The fingerprint system can be said to be very effective in implementing discipline, while the manual system can be said to be effective but must be closely monitored by related parties. The results of the effectiveness research were analyzed with four indicators of effectiveness, namely: 1) program understanding, 2) target accuracy, 3) timeliness, and 4) goal achievement. The application of discipline on the part of both permanent employees and interns can be said to be disciplined, this can be seen in the following three discipline indicators: 1) attendance rate, 2) punishment, and 3) reward/compensation.